Perception of the students' towards the effectiveness of security department in UiTM Shah Alam / Evelyn Grunsin - Grunsin, Evelyn; Lamejah, Herdayani (2008)
Perception of the students is various and differs from each other. Thus, the study examines the student's perception as the tools to see to what extend the Security Departments was being perceived from the standpoint related to the student's experience and their year in campus.